Antioxidants: Reduces the Male Infertility - Prih Bashir, Asma Jalbani, Farah Siraj, Ayesha Jalbani, Parisa Bashir, Ufaque Batool K. Samo, , Israr Ahmed Jalbani, M. Khan Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study takes a microscopic overview of main semen parameters such as sperm motility, morphology, fertility rate, sperm concentration, and DNA damage and their relationship with antioxidants. Aim: To explain the role of antioxidant minerals including Vitamin E and C, N-Acetyl cysteine, Selenium, Carnitine, CoQ10, and Zinc in improving semen quality across the semen parameters. Methods: The design of the study is an in-depth review and analysis of minerals that improve semen quality. Results: The result derived from this study stipulates those aforementioned minerals enhance the overall health and wellbeing of the body, which results in the semen quality improvement. The study determines that it is indeed true that antioxidant supplementation for infertile males produces favorable results. The practical implications: are immense including early diagnosis and treatment of infertility. Conclusion: To conclude, supplements such as CoQ10 improve sperm count, the combined dosage of Vitamin C and E diminishes sperm damage, and carnitine enhances sperm morphology and mobility. The study also concludes that with males who have infertility because of Oxidative Stress, the above-mentioned antioxidants produce a positive result. Keywords: Vitamin C and E, Selenium, Carnitine CoQ10, Zinc, Acetyl Cysteine